Light exposure during development affects physiology of adults in Drosophila melanogaster - Damulewicz, Milena; Tyszka, Aleksandra; Pyza, Elzbieta (Frontiers in Physiology, 2022)
Light is one of most important factors synchronizing organisms to day/night cycles in the environment. In Drosophila it is received through compound eyes, Hofbauer-Buchner eyelet, ocelli, using phospholipase C-dependent phototransduction and by deep brain photoreceptors, like Cryptochrome. Even a single light pulse during early life induces larval-time memory, which synchronizes the circadian clock and maintains daily rhythms in adult flies. In this study we investigated several processes in adult flies after maintaining their embryos, larvae and pupae in constant darkness (DD) until eclosion. We found that the lack of external light during development affects sleep time, by reduction of night sleep, and in effect shift to the daytime. However, disruption of internal CRY- dependent photoreception annuls this effect. We also observed changes in the expression of genes encoding neurotransmitters and their receptors between flies kept in different light regime. In addition, the lack of light during development results in decreasing size of mushroom bodies, involved in sleep regulation. Taking together, our results show that presence of light during early life plays a key role in brain development and affects adult behavior.